Was ist aufklärung?: Génesis del canon burgués de universalidad ante rem - Llamas Roig, Vicente (Cauriensia, 2023)
An emerging social class, the bourgeoisie, whose hegemony would be consolidated in the 17th-18th centuries, woke up from the dogmatic dream imposing a new worldview that dominated the secular philosophical scene. Proven to be crucial for it the epistemicide of the Platonic νοητόν, successively transvalued into a ratio exemplar in the divine mind and an innate idea in the human intellect with the shift from medieval theocentrism to modern anthropocentrism. The epistemological paradigm that was the aristocratic νοητόν or its subsequent variations in the "noble" optics of Scholasticism and Rationalism granted this Platonic paradigm an universal position ante rem sensibilem. The influence of eighteenth-century insular Empiricism in continental thought will precipitate its gnoseological distortion as a νοούμενoν by transfer to the sphere of practical reason. The θεωρία - πρᾱξις pulse opts for the latter in the bourgeois order, redefining universality ante rem in an ethical key, to the detriment of its epistemological - intellective position. The only admissible ante rem sensibilem universality in this new ideological context will be that of the moral imperative and a priori practical judgments supported by νοούμενα (entia rationis without ontological consistency or epistemological value) due to the empirical disinterest of the will. The categories of the intellect, a priori forms of abstractive intelligibility (non-intuitive) operate on sensitive data, provide universality post rem. Reason (Vernunft) retains the alleged bifaciality of the intellect (Verstand), a theoretical face ordered to the φαινομένον (objective onto-epistemological dimension of being) and a practical facet that will support the νοούμενoν (strictly rational dimension of the entity that rescues man from the regime of natural causality in his illusion of freedom, grounded on the noumenal subsidy). Finally, the blurring of noumenon in the irrationality of a blind force will make it a τρóφημα, inaugurating the era of the id, the solstice of monofacial reason.